Economic performance of private and public sugar estates, Sudan, 1990-2008 - Elzebair, Selwa Ahmed; Ahmed, Mudather; Elamin, Abbas Elsir (Gezira Journal of Agricultural Science; Vol 13 No 2 (2015), 2015)
Local sugar production is considered an important import substitution strategy. The government policies encourage expansion in sugar production. As a result, many sugar estates are established under private and public systems. This study was aimed at assessing the economic efficiency of the sugar estates. Purposive sampling was used to select three sugar estates namely; Kenana as a private estate, Guneid as a public estate operated by tenants and Sennar as a public estate operated by direct labor. Secondary data from the records of these estates were  used to achieve  the stated objectives. Descriptive statistics, frequencies and benefit cost ratio were the main analytical tools used in this study. Results showed apparent increase in the cultivated area, yield and production of sugar during the last decade. Also, results showed that Kenana is attaining the  highest yield, relatively lower cost, highest revenues and the highest benefit cost ratio, indicating more efficiency in sugar production than Sennar  and Guneid  during the period (1990-2008).      يعتبر إنتاج السكر المحلي إستراتيجية مهمة لوقف استيراده. ولذلك تشجع السياسات الحكومية التوسع في إنتاج السكر بالقطاعات الخاصة والعامة. هدفت هذه الدراسة إلي تقييم الكفاءة الاقتصادية لقطاعات السكر وتم اختيار شركة سكر كنانة ممثلة للقطاع الخاص ومصنع الجنيد كمثال للقطاع العام الذي يعمل بواسطة المزارعين ومصنع سكر سنار كمثال للقطاع العام ـأيضاً ولكنه يعمل بالعمالة المباشرة . للوصول إلي هدف هذه الدراسة تم جمع معلومات ثانوية من التقارير والسجلات الموجودة في الثلاث مصانع والدراسات الأخرى ذات الصلة, استخدم التحليل الإحصائي الوصفي وتحليل العائدات والتكاليف لتحليل البيانات ، أوضحت نتائج هذه الدراسة أن هنالك زيادة في المساحة المزروعة بالقصب وزيادة في انتاج وإنتاجية السكر في كل القطاعات خلال العقد الماضي ,وأن كنانة تنتج أعلي انتاجية  مع أقل تكاليف وبها أعلي ايراد أيضاً وأن معدل العائد على التكاليف كان أعلى في كنانة وهذا يدل علي أن كنانة أكثر كفاءة من سنار والجنيد في إنتاج السكر في الفترة من 1990 إلي 2008.